Analysis Neutrophil-to-Lymphocyte and Monocyte-to- Lymphocyte Ratios in Pediatric Respiratory Infections - Suraidah, Suraidah; Handayani, Irda; Kadir, Nursin Abdul (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Indonesia ranks third among countries with the highest tuberculosis (TB) cases worldwide. Pneumonia also stands as a leading cause of death among infants in developing nations. The delay in diagnosing and the challenges in distinguishing TB and pneumonia have significant impacts on elevated morbidity and mortality rates. Both Neutrophil-to-Lymphocyte Ratio (NLR) and Monocyte-to-Lymphocyte Ratio (MLR) serve as inflammatory biomarkers utilized for rapid and straightforward bacteremia evaluation. This study aimed to analyze the difference between NLR and MLR in diagnosing of TB and pneumonia in children. This study was retrospective cross-sectional research utilizing secondary data at the time of initial diagnosis by a clinician as TB or pneumonia. Subjects with TB and/or pneumonia were treated at Dr. Wahidin Sudirohusodo Hospital, Makassar from January 2017 to December 2021. The research sample consisted of 150 patients with pediatric patients with pneumonia. Statistical analyses involved the Kolmogorov-Smirnov test, Mann-Whitney U test, and Receiver Operating Characteristic (ROC). This study examined NLR and MLR as supportive biomarkers for diagnosing TB and pneumonia. The NLR (AUC 0.674) and MLR (AUC 0.63) values in TB subjects were reasonably good in distinguishing between TB diagnosis and healthy subjects. The NLR (AUC 0.77) and MLR (AUC 0.787) values were effective in distinguishing pneumonia diagnosis from healthy control with better sensitivity and specificity compared to TB subjects. However, NLR (AUC 0.401) and MLR (AUC 0.384) values were not recommended to distinguish pneumonia from tuberculosis due to low AUC and extremely low sensitivity and specificity. The NLR and MLR values cannot be used to differentiate TB and pneumonia in children due to their low sensitivity and specificity.